Characterization of plastic debris from surface waters of the eastern Arabian Sea–Indian Ocean. (August 2021) - Naidu, S.A.; Mawii, L.; Ranga Rao, V.; Anitha, G.; Mishra, P.; Narayanaswamy, Bhavani E.; Anil Kumar, V.; Ramana Murthy, M.V.; GVM, Gupta
Abstract: The quantity of floating plastic debris (FPD) is continuously being increased in the oceans. To assess their size, structure, and composition along the eastern Arabian Sea (EAS), FPD samples were collected by using a surface plankton net. The microplastic size fraction (0.5–5 mm) was the most prevalent accounting for >50% of the total, followed by mesoplastics (5–25 mm; ~40%) and macroplastics (>25 mm; ~10%). The collected FPDs were categorized into five different types and eight colours. Attenuated Total Reflectance-Fourier Transform Infrared Spectrometry (ATR-FTIR) analysis of the plastics revealed that polypropylene, polyethylene, and nylon were the most dominant polymers, and these comprised mostly of fibre/fishing line. The abundance of FPD in the EAS (0.013 ± 0.012 no.s/m 3 ) was found to be very low compared to elsewhere. The prevalent microplastics presence in the oceans might have occurred mainly by the degradation of larger items. It increases bioavailability, and hence, is a risk to marine ecosystems. Graphical abstract: Unlabelled Image Highlights: Basic data regarding the characterization of plastic debris along the EAS. The microplastic size fraction (0.5-5mm) was the most prevalent accounting for >50% of the total, followed by mesoplastic and macroplastic. The prevalent microplastic presence in the oceans might have occurred mainly via the degradation of larger items. Polypropylene, polyethylene and nylon were the most dominant polymers. Plastics comprised mostly of fibre/fishing line. The plastic debris in the EAS (0.013 ± 0.012 no.s/m 3 ) was found to be very low comparied to elsewhere.